2011
DOI: 10.1002/joc.2174
|View full text |Cite
|
Sign up to set email alerts
|

A spatial regression analysis of the influence of topography on monthly rainfall in East Africa

Abstract: Precipitation in Kenya is highly variable and dominated by a variety of physical processes. Statistical studies of climate patterns have historically focused on application of ordinary least squares (OLS) regression to test hypotheses related to multiple predictive variables, perhaps in an attempt to better understand the physical mechanisms that drive precipitation, or on use of spatially explicit models, typically kriging-or spline-based analyses, for the purpose of improving predictions. Each of these appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 28 publications
(43 reference statements)
0
48
0
2
Order By: Relevance
“…Koinrad, II [60] also found that elevation is strongly associated with light precipitation events. Hession and Moore [61] found that rainfall was strongly influenced by elevation and slope during the 'long rains' and 'short rains'. In this study, elevation was not found to be a significant effect on the change of extreme precipitation except for PRCPTOT, which was similar to the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…Koinrad, II [60] also found that elevation is strongly associated with light precipitation events. Hession and Moore [61] found that rainfall was strongly influenced by elevation and slope during the 'long rains' and 'short rains'. In this study, elevation was not found to be a significant effect on the change of extreme precipitation except for PRCPTOT, which was similar to the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo y con el propósito de determinar si la σ 2 analytically expressed as ε~iidN(0, σ 2 ). To verify these assumptions were respectively applied the following tests Durbin-Watson statistics and Kolmogorov-Smirnov widely described by Marquínez et al (2003), while the homogeneity of variance was evaluated graphically, verifying the absence of any systematic pattern or trend between errors and model predictions as suggested Hession and Moore (2011).…”
Section: Validación Estadística De Las Interpolacionesmentioning
confidence: 99%
“…The method allows to include all independent variables in a single step and subsequent steps discard variables that do not meet the expected level of statistical significance (p <.05). Every time a variable is removed from the function, the model is adjusted and the value of R 2 resulting overall variance explained, further details of the process are described by Marquínez et al (2003) and Hession and Moore (2011).…”
Section: Validación Estadística De Las Interpolacionesmentioning
confidence: 99%
“…Topographic attributes such as elevation and aspect have been revealed to have a great influence on the patterns and distribution of vegetation in mountainous areas [10,11]. Therefore, it is of great importance to evaluate the role of climate and topography in shaping the spatial distribution of vegetation at high altitudes, with respect to different vegetation cover types [12].…”
Section: Introductionmentioning
confidence: 99%